Analysis of Factors Influencing Stability of Overlying Soil Layer on Thin Bedrock Based on Crack Development-Closure Test - Guangming Wu; Haibo Bai; Luyuan Wu; Shixin He; Bin Du (Advances in Civil Engineering)
The water-blocking properties of the clay layer at the bottom of the Cenozoic overburden in China are an important factor influencing the safety of thin bedrock coal seam mining. Clay has remolding properties that are unlike the nonreversible characteristics of cracks in brittle rock, and failure cracks in clay can reclose or continue to expand under the influence of different external factors. In this work, the soil layer on top of thin bedrock is the research object, and the influences of the particle composition, water content, soil layer thickness, and crack width on the crack development-closure state of soil layer are analyzed by the orthogonal test method. Visual analysis shows that the order of influence of each factor on the stability of soil layer is the crack width, particle composition, soil layer thickness, and water content. The stability of soil layer decreases with increasing crack width and sand content and decreasing soil layer thickness; in addition, soil layer stability decreases first and then increases with increasing water content. Further variance analysis shows that the crack width and particle composition are key factors that impact the stability of soil layer and that the soil layer thickness has some influence, while the water content has little effect on the stability of soil layer. In addition, the crack will reclose when the sand content in soil is less than 50% and the crack width is less than or equal to 1.0 mm, and the soil layer is prone to further failure when the sand content in soil is more than 50% and the crack width is greater than or equal to 3.0 mm; when the soil layer thickness is 15.0 cm, its stability is better than when the soil layer thickness is 10.0 cm or 5.0 cm.